PRODUCT INNOVATION AND THE COMPETITIVE ADVANTAGE - Reguia, Cherroun (European Scientific Journal, ESJ, 2014)
Innovation is considered as one of the success features in the economic companies, it’s regarded as the basic element to reach customer satisfaction and to realize their desires. It means finding a new idea which will be implemented for realizing the competitive advantage to the companies, at a time when they have had similar opportunities to present their products with low costs. We will try through this paper to highlight the innovation in products field through the following: Definition of innovation and creativity in the economic companies; Products innovation: types, stages and features: The role of the products innovation in realizing competitive advantage.